2022
DOI: 10.1111/jonm.13644
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies that motivated frontline nurses while caring for the COVID‐19 patients during the pandemic: A scoping review

Abstract: Background The world faced a great health crisis during the covid‐19 pandemic. Consequently, the healthcare providers struggled and faced tremendous difficulties in treating high‐load critical patients. This was particularly true in low‐ and middle‐income countries where the work and patient loads are always higher and nurses at the forefront must deal with emergencies while being at high risk of exposure. However, little is known about the survival strategies of frontline nurses as dealt with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Although these study participants relied on self-care coping strategies, several described developing new strategies and rituals for taking care of themselves. Similar qualitative evidence uncovered healthcare professionals' self-strategies to deal with difficult situations (11,42,47,51). These strategies help nurses and nursing assistants to become more professional and inspire them in mindfulness.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Although these study participants relied on self-care coping strategies, several described developing new strategies and rituals for taking care of themselves. Similar qualitative evidence uncovered healthcare professionals' self-strategies to deal with difficult situations (11,42,47,51). These strategies help nurses and nursing assistants to become more professional and inspire them in mindfulness.…”
Section: Discussionmentioning
confidence: 64%
“…They got new information online, followed infection control procedures, and used appropriate PPE and protection techniques to reduce stress. Literature data also show that access to reliable information is the most common way of reducing adverse consequences of distress and maintaining a sense of security ( 39 , 42 , 47 ). Similar to previous studies, our study participants used positive attitudes, clear hospital policies, and infection prevention knowledge to reduce team stress during the COVID-19 outbreak, helped their colleagues by teaching them updated skills and techniques, and provided a team approach ( 16 , 41 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the coping strategy, more than 70% of nurses considered talking to family and friends as the most effective way to deal with stress. Friends/family members are usually seen as important sources of social support for they could provide comfort, offer constructive advice and reduce negative feelings (Liu & Aungsuroch, 2019; Rony et al, 2022; Woodhead et al, 2016). Our finding that talking to with family and friends was significantly associated with lower turnover intention confirmed the positive role of social support in decreasing nurses' intention to leave the profession (Fronda & Labrague, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The current study revealed that nurses could maintain self‐control while caring for COVID‐19 patients amid the terrible pandemic. Emotional self‐control enables nurses to handle their job workloads better and develop self‐confidence and self‐resilience (Hatami et al, 2022 ; Rony et al, 2022 ). It can help resolve work‐related conflicts by developing work engagement, empathy for patients and passion for nursing tasks in the clinical setting (Cuartero & Tur, 2021 ).…”
Section: Discussionmentioning
confidence: 99%